Pengembangan Model Program Ekstrakurikuler Futsal Adaptif untuk Mendukung Kepercayaan Diri Siswa dengan Hambatan Fisik: Development of an Adaptive Futsal Extracurricular Program Model to Support the Self-Confidence of Students with Physical Disabilities - Bakti Djailani; Pujaningsih Pujaningsih (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
This study aimed to develop an adaptive futsal extracurricular program model to support the self-confidence of students with physical disabilities at SMP Negeri 3 Sangatta Utara. The study employed a limited-scale Research and Development (R&D) method using the ADDIE model, comprising the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of a Physical Education, Sports, and Health (PJOK) teacher—who also served as the extracurricular supervisor—acting as the practitioner, and one student with a physical disability serving as the subject for the limited trial. Data were collected through observation, interviews, documentation, practitioner assessment questionnaires, practicality questionnaires, and self-confidence behaviour observation sheets. The data were analysed using simple qualitative and quantitative descriptive techniques. The results indicated that the developed product—an adaptive futsal extracurricular program model consisting of six activity sessions—was deemed suitable for use based on instrument validation results, receiving a practitioner rating of 73% (categorised as "suitable"). The product also achieved a practicality score of 75% (categorised as "practical"), while program implementation rates ranged from 69% to 75% across the sessions. Furthermore, observations revealed a trend of increasing self-confidence behaviour in the student, rising from 31% in the initial session to 64% in the final session. Thus, the adaptive futsal extracurricular program model is considered suitable and practical, and it holds the potential to serve as an implementation guide for extracurricular activities that support the development of self-confidence among students with physical disabilities in inclusive schools.